1979
DOI: 10.1177/27.9.383829
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative immunoperoxidase procedure employing energy dispersive x-ray analysis.

Abstract: A method is described for substituting gold for osmium as a marker in the unlabeled antibody technique. The gold marker can be detected in the light or electron microscope. The gold-labeled reaction product can be detected in lower concentrations than osmium and can be used as the basis for quantitating antigen concentrations in cells and tissues with the scanning electron microscope and energy dispersive x-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The use of gold as an immunostaining agent was first documented in 1971 when Faulk and Taylor used antibody coated AuNPs to visualise specific antigens using TEM [392]. Relying on the 'lock and key' mechanisms of antibody-antigen interactions in combination with the high electron density properties of gold, immunolabelling methods have expanded with multiple labelling possibilities (using different sized AuNPs) [393], and adaptations have been made for visualisation using SEM [394,395] and dark field microscopy [374].…”
Section: Gold Nanoparticles As Bioimaging Agentsmentioning
confidence: 99%
“…The use of gold as an immunostaining agent was first documented in 1971 when Faulk and Taylor used antibody coated AuNPs to visualise specific antigens using TEM [392]. Relying on the 'lock and key' mechanisms of antibody-antigen interactions in combination with the high electron density properties of gold, immunolabelling methods have expanded with multiple labelling possibilities (using different sized AuNPs) [393], and adaptations have been made for visualisation using SEM [394,395] and dark field microscopy [374].…”
Section: Gold Nanoparticles As Bioimaging Agentsmentioning
confidence: 99%
“…In immunohistochemical staining, DAB is known to be oxidized by hydrogen peroxide (H 2 O 2 ) in the presence of HRP that forms a brown deposition, representing the location of the HRP for light microscopy. Intensifications of DAB deposition sites have been reported with various heavy metallic ions as well as gold chloride 19 , 20 , 22 25 . The crucial binding ability between gold chloride and the immunochemical reaction product of DAB has been indicated by energy dispersive X (EDX)-ray analysis 25 .…”
Section: Resultsmentioning
confidence: 99%
“…It is conceivable that all metal salts bind to polyDAB but that the co‐ordination chemistry of the product dictates whether it is catalytic or not. For example, both gold (Siegesmund et al , 1979; Newman et al , 1983a) and platinum (de Bruijn et al , 1986; Hiraoka & Hirai, 1992, 1995) salts have been demonstrated to bind to polyDAB and both promote the catalysis of silver reduction. By contrast, phosphotungstic acid has been reported to increase the electron opacity of polyDAB (Newman et al , 1983a) but was not observed to catalyze silver reduction in the experiments reported here.…”
Section: Discussionmentioning
confidence: 99%